2021
DOI: 10.3390/medicina57111151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Cetuximab and Paclitaxel after Progression on Immune Checkpoint Inhibitors in Recurrent or Metastatic Head and Neck Squamous Cell Carcinoma

Abstract: Background and Objectives: In recent years, the effectiveness of chemotherapy after immune checkpoint inhibitor administration has attracted attention in various cancers, including head and neck cancers. However, individual assessments of the administered chemotherapy regimens are insufficient. This study aimed to evaluate the efficacy and safety of chemotherapy after immune checkpoint inhibitor administration in recurrent metastatic head and neck cancer by focusing on a single regimen. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Although our results cannot be compared to those from a large phase III trial, the fact that only half of the patients in Keynote-048 received second-line therapy after IO, while in the current study the median number of treatment lines before pembro + CP was 3, with up to 80% of our patients receiving prior therapy with anti-PD(L)1 agents, may explain the prolonged survival times achieved (2). Indeed, prospective, and retrospective evidence suggests sequential treatment with ICIs followed by salvage chemotherapy associates with longer survival (22)(23)(24)(25)(26)(27). In addition, the use of ICI rechallenge may also allow to improve outcomes in patients with R/M SCCHN and in other entities such as NSCLC (25,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results cannot be compared to those from a large phase III trial, the fact that only half of the patients in Keynote-048 received second-line therapy after IO, while in the current study the median number of treatment lines before pembro + CP was 3, with up to 80% of our patients receiving prior therapy with anti-PD(L)1 agents, may explain the prolonged survival times achieved (2). Indeed, prospective, and retrospective evidence suggests sequential treatment with ICIs followed by salvage chemotherapy associates with longer survival (22)(23)(24)(25)(26)(27). In addition, the use of ICI rechallenge may also allow to improve outcomes in patients with R/M SCCHN and in other entities such as NSCLC (25,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…In the Keynote-B10 study mentioned before, there were no differences between using three-weekly paclitaxel (175 mg/m 2 d1) and weekly paclitaxel (100 mg/m 2 d1,8), suggesting that weekly paclitaxel may be similar in terms of efficacy with a potentially more favourable toxicity profile (11). Interestingly, taxane-based weekly chemotherapy combined with cetuximab after progression to ICIs has been reported to achieve higher responses with a favorable impact in survival compared to historical data from the pre-ICI era (22)(23)(24)(25)(26)(27). For all these reasons, weekly taxane-based chemotherapy should be further evaluated -and compared with three-weekly taxane-based regimens (either in combination or sequentially with anti-PD(L)1 agents in R/M SCCHN).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the positioning of weekly paclitaxel plus cetuximab as a 2L scheme in the immunotherapy era, Suzuki et al (18) published in 2021 a study using this regimen in eighteen R/M HNSCC patients after progression following immune checkpoint inhibitor (ICI) therapy. This study showed a median PFS and OS of 3.8 months and 9.6 months, respectively (18).…”
Section: Overall Survival With Weekly Paclitaxel Plus Cetuximab A) In...mentioning
confidence: 99%
“…Regarding the positioning of weekly paclitaxel plus cetuximab as a 2L scheme in the immunotherapy era, Suzuki et al (18) published in 2021 a study using this regimen in eighteen R/M HNSCC patients after progression following immune checkpoint inhibitor (ICI) therapy. This study showed a median PFS and OS of 3.8 months and 9.6 months, respectively (18). In this sense, Sato et al (19) in a retrospective study in patients with R/M head and neck cancer showed that the sequential treatment with anti-PD-1 therapy followed by paclitaxel-based chemotherapy could be a good strategy to maximize the efficacy of chemotherapy in this type of patients.…”
Section: Overall Survival With Weekly Paclitaxel Plus Cetuximab A) In...mentioning
confidence: 99%
See 1 more Smart Citation